Quality of care of Egyptian asthmatic children: Clinicians adherence to asthma guidelines - Salama Ashraf A; Mohammed Ahmed A; El okda El Sayed E; Said Rasha M (BMC, 2010)
Abstract Background Despite the development and dissemination of guidelines for the diagnosis and management of asthma, a gap remains between current recommendations and actual practice. Objectives To assess the physicians attitude towards asthma guidelines and their adherence to its recommendations. Methods Three hundred and fifty two clinicians (101 General practitioners, 131 pediatric specialists, 35 pediatric consultants and 85 doctors did not report the qualification) engaged in direct childhood asthma care in Cairo, Egypt were subjected to a self-administered questionnaire with 35 questions of which most were multiple choices, aiming at assessment of three important aspects about the involved physicians; physician's knowledge, practice and attitude. 165 of the clinicians were working in governmental hospitals, 68 clinicians work in private clinics and 119 clinicians work in both. Results Agreement with asthma guidelines was present in 76.2% of the studied physicians, however those who not in agreement with the guidelines claimed that this was mainly due to patient factors, firstly the poor socioeconomic standard of the patient (18.1%) and secondly due to poor patient compliance (16%). Poor knowledge was found in 28.5%, poor practice was found in 43.6% and poor attitude was found in 14.4% of the studied physicians. There was positive highly significant correlation between qualification and knowledge, (p < 0.01), positive highly significant correlation between qualification and practice, (p < 0.01), and positive highly significant correlation between qualification and attitude, (p < 0.01). Conclusion The attitude of the studied physicians revealed agreement of their majority with the guidelines, while the disagreement was mainly explained by the poor socioeconomic standard of the patients. The degree of poor practice is more marked than that of poor knowledge or poor attitude reflecting resources limitations and applications obstacles in the physician's practice.